Avoiding and treating dental complications : best practices in dentistry - Termeie, Deborah (Wiley Blackwell, 2016)
Complications from dental procedures are inevitable and encountered by all dental professionals. 'Avoiding and Treating Dental Complications' is designed to address proper management of these situations in everyday practice.